Evaluasi Usability Pada Aplikasi M-Pise LPD Digital Di Kabupaten Jembrana dengan Metode Usability Testing - Putu Ary Indra Pratama; Nengah Widya Utami; Putu Trisna Hady Permana S (Universitas Wahid Hasyim, 2023)
This study aims to evaluate usability on the user's M-Pise LPD Digital application page in Jembrana Regency by using the usability testing method with Performance Measurement and RTA (Retrospective Think Aloud) techniques. The usability aspects reviewed are effectiveness, efficiency, and user satisfaction. In this study there were 20 respondents who were involved consisting of a group of advanced respondents and a group of novice respondents. The results showed that (1) the M-Pise LPD Digital application was still not effective when viewed from errors (errors) when the respondent was doing the task, (2) the M-Pise LPD Digital application in terms of efficiency has proven to be efficient seen from statistical testing Mann Whiteney showed that there was no difference in time between the beginner and advanced groups of respondents so that it could be said to be efficient, (3) User satisfaction was still unsatisfied as seen from the SUS questionnaire score of 64. Thus the M-Pise application page did not have good usability. Thus the recommendations for improvement given are based on the results of performance measurements, namely errors. Recommendations for improvement will focus on improving menu components and features. Meanwhile, based on the results of the problems and suggestions for the results of the RTA, namely simplification of features and improvements as well as clarity of the layout of letters, numbers and icons.